Whittington [compact disc, unabridged] - Armstrong, Alan., 1939- (Random House/Listening Library, 2006)
Whittington, a feline descendant of Dick Whittington's famous cat of English folklore, appears at a rundown barnyard plagued by rats and restores harmony while telling his ancestor's story.